CaMKIIδ subtypes differentially regulate infarct formation following ex vivo myocardial ischemia/reperfusion through NF-κB and TNF-α. (February 2017) - Gray, Charles B.B.; Suetomi, Takeshi; Xiang, Sunny; Mishra, Shikha; Blackwood, Erik A.; Glembotski, Christopher C.; Miyamoto, Shigeki; Westenbrink, B. Daan; Brown, Joan Heller
Abstract: Deletion of Ca 2+ /calmodulin-dependent protein kinase II delta (CaMKIIδ) has been shown to protect against in vivo ischemia/reperfusion (I/R) injury. It remains unclear which CaMKIIδ isoforms and downstream mechanisms are responsible for the salutary effects of CaMKIIδ gene deletion. In this study we sought to compare the roles of the CaMKIIδB and CaMKIIδC subtypes and the mechanisms by which they contribute to ex vivo I/R damage. WT, CaMKIIδKO, and mice expressing only CaMKIIδB or δC were subjected to ex vivo global ischemia for 25 min followed by reperfusion. Infarct formation was assessed at 60 min reperfusion by triphenyl tetrazolium chloride (TTC) staining. Deletion of CaMKIIδ conferred significant protection from ex vivo I/R. Re-expression of CaMKIIδC in the CaMKIIδKO background reversed this effect and exacerbated myocardial damage and dysfunction following I/R, while re-expression of CaMKIIδB was protective. Selective activation of CaMKIIδC in response to I/R was evident in a subcellular fraction enriched for cytosolic/membrane proteins. Further studies demonstrated differential regulation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling and tumor necrosis factor alpha (TNF-α) expression by CaMKIIδB and CaMKIIδC . Selective activation of CaMKIIδC was also observed and associated with NF-κB activation in neonatal rat ventricular myocytes (NRVMs) subjected to oxidative stress. Pharmacological inhibition of NF-κB or TNF-α significantly ameliorated infarct formation in WT mice and those that re-express CaMKIIδC, demonstrating distinct roles for CaMKIIδ subtypes in I/R and implicating acute activation of CaMKIIδC and NF-κB in the pathogenesis of reperfusion injury. Highlights: CaMKIIδB and CaMKIIδC differentially regulate ischemia/reperfusion injury. CaMKIIδC is selectively activated during ischemia/reperfusion. NF-κB activation during I/R is exacerbated by CaMKIIδC expression. Inhibition of NF-κB or TNF-α blocks CaMKIIδC -mediated ischemia/reperfusion injury.